ON FRACTIONAL q−KINETIC EQUATION - Garg, Mridula; Chanchlani, Lata (Matematichki Bilten, 2012)
In this paper, we obtain the solution of fractional \(q\)-kinetic equation, which involves the Riemann-Liouville fractional \(q\)-integral operator. We apply the method of \(q\)-Laplace transform and its inverse to obtain the solution in closed form. The solutions of ordinary \(q\)-kinetic equation and two more fractional \(q\)-kinetic equations are obtained as special cases of our main result. We have also drawn some graphs of the solutions of fractional \(q\)-kinetic equations using the software MATHEMATICA.